2014
DOI: 10.1159/000360738
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Anxiety Disorders and Temperament

Abstract: Background: The aims of the present study were to explore whether symptoms in different anxiety disorders are associated with Cloninger's model temperament dimensions novelty seeking (NS), harm avoidance (HA), reward dependence and persistence compared with control subjects in clinical samples of adults or late adolescents. Method: Literature search in the following databases: Cochrane Library, PubMed (Medline), Web of Science, Psycinfo and PsycArticles. Systematic review, grading the level of evidence and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 148 publications
7
47
0
Order By: Relevance
“…One explanation could be that higher obsessive-compulsive symptoms reflect a disposition towards harm avoidance type temperament. Meta-analyses have demonstrated that harm avoidance is more common in women,39 and also that harm avoidance links OCD, panic disorder, and social anxiety disorder 40…”
Section: Discussionmentioning
confidence: 99%
“…One explanation could be that higher obsessive-compulsive symptoms reflect a disposition towards harm avoidance type temperament. Meta-analyses have demonstrated that harm avoidance is more common in women,39 and also that harm avoidance links OCD, panic disorder, and social anxiety disorder 40…”
Section: Discussionmentioning
confidence: 99%
“…Increased ERN amplitudes are not OCD specific and were observed in generalized anxiety disorder (GAD, e.g., Weinberg, Olvet, & Hajcak, ; Xiao et al, ), social anxiety (e.g., Endrass et al, ), health anxiety (Riesel et al, ), and less consistently in depression (Gillan et al, ; Manoach & Agam, ). These disorders are frequently comorbid (Kessler et al, ; Krueger & Markon, ; Ruscio et al, ) and share clinical features such as heightened harm avoidance (Kampman, Viikki, Jarventausta, & Leinonen, ), worry (Dar & Iqbal, ; Yook, Kim, Suh, & Lee, ), reassurance seeking and checking behavior (Halldorsson & Salkovskis, ; Kobori & Salkovskis, ; Weinberg, Kotov, & Proudfit, ). These symptoms have also been related to hyperactive neural error signals (e.g., Cavanagh & Shackman, ; Moser et al, ; Weinberg, Kotov et al, ).…”
Section: Section 2: Enhanced Neural Error Signals As Endophenotype Fomentioning
confidence: 99%
“…SAD and AN additionally share preoccupation with how one is perceived by others as a central feature [35]. Anxious personality traits, including elevated neuroticism, perfectionism and harm avoidance as well as decreased novelty-seeking are frequently observed in OCD, SAD and AN [12,13] and may represent a common pathway for the development of both anxiety disorders and AN. In AN, anxious, perfectionistic and obsessional personality traits appear to underlie heritability [32,36], worsen with starvation [37][38][39], persist after recovery [4,[40][41][42] and portend a poorer prognosis [43].…”
Section: Phenomenological Overlap and Comorbidity Between An And Anximentioning
confidence: 99%
“…The successful treatment of AN may well require both interruption of excessive exercise and dietary restraint, as well as extinction of the heightened A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 13 anxiety and meal avoidant behaviors that characterize the disorder. Indeed, pre-meal anxiety has been found to be inversely related to food intake at a standardized meal in individuals with AN [101].…”
Section: Implications For Treatmentmentioning
confidence: 99%
See 1 more Smart Citation